2007
DOI: 10.2522/ptj.20060343
|View full text |Cite
|
Sign up to set email alerts
|

Berg Balance Scale: Intrarater Test-Retest Reliability Among Older People Dependent in Activities of Daily Living and Living in Residential Care Facilities

Abstract: Despite a high ICC value, the absolute reliability showed that a change of 8 BBS points is required to reveal a genuine change in function among older people who are dependent in activities of daily living and living in residential care facilities. This knowledge is important in the clinical setting when evaluating an individual's change in balance function over time in this group of older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
117
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 25 publications
5
117
1
2
Order By: Relevance
“…Interestingly, our MDC values are comparable to previous studies of BBS in stroke patients where a score difference of 7 is necessary to be 95% confident of a genuine change [34,35]. Although the 95% confidence level is the most common level in research, some authors believe that lower levels of confidence might be enough in clinical settings [29,34,36]. Hence, we also present the 90% and 80% levels of confidence to provide the clinician with more options when evaluating an individual patient's function and to pinpoint the difference of increasing statistical rigor.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, our MDC values are comparable to previous studies of BBS in stroke patients where a score difference of 7 is necessary to be 95% confident of a genuine change [34,35]. Although the 95% confidence level is the most common level in research, some authors believe that lower levels of confidence might be enough in clinical settings [29,34,36]. Hence, we also present the 90% and 80% levels of confidence to provide the clinician with more options when evaluating an individual patient's function and to pinpoint the difference of increasing statistical rigor.…”
Section: Discussionsupporting
confidence: 84%
“…The SEM% value of the total score was below 7, which is considered small [28]. To our knowledge, there is no clear definition of acceptable MDC "cut-off" values and in addition, several different terms represent similar calculations [29][30][31]. For example, the MDC% is defined exactly the same way as the smallest real difference in percentage (SRD %) [30].…”
Section: Discussionmentioning
confidence: 99%
“…[3] As age advances people experience www.jmscr.igmpublication.org Impact Factor 5.84 Index Copernicus Value: 83.27 ISSN (e)-2347-176x ISSN (p) 2455-0450 DOI: https://dx.doi.org/10.18535/jmscr/v5i2.158 changes in their entire body, from the CNS level up till their organ level, hence it has been found that due to aging processes balance often is impaired among geriatric population which happens to be one of the major concerns that makes them prone to falls and secondary complications of falls which can lead to high rates of morbidity and mortality, (1,2) also leads to dramatic consequences, such as dependency in activities of daily living (ADL), admission to nursing homes and fractures. Most of these factors are said to occur due to complex interactions between multiple risk factors which include muscle weakness, gait deficit, age over 80 years, visual deficits, cognitive impairments, history of falls, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Intratester and intertesterreliability have been reported as high in geriatric populations. (N=10-30) (ICC= .99, [16] ICC [3,1]=.92-.96, [17] ICC= [3,3] = .98. [15] The test ret set reliability of measurements obtained from group of adults without cognitive impairments (n=844, age range of total sample [N=2,305]=69-104 years) was moderate(ICC [model not stated]= .56).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies reported the relative reliability of physical performance measures among adults with dementia (Binder, Miller, & Ball, 2001;Blankevoort et al, 2010;Blankevoort et al, 2013;Conradsson et al, 2007;Lin et al, 2004;Ries, Echternach, Nof, & Gagnon, 2009;Rockwood, Awalt, Carver, & MacKnight, 2000;Suttanon et al, 2011;Tappen, Roach, Buchner, Barry, & Edelstein, 1997; V. Thomas & Hageman, 2002;van Iersel et al, 2007), most have failed to assess the absolute reliability, the measure of magnitude of change and individual variability.…”
Section: Introductionmentioning
confidence: 99%